Entrepreneurial Competency as Determinant for Success of Female Entrepreneurs in Nigeria - Kabir, Mohammed; Ibrahim, Hazril Izwar; Mohammad Shah, Khairul Anuar (Bogor Agricultural University, 2017)
This study aimed at examining the direct relationship between entrepreneurial competency and firm performance of female Entrepreneurs in Nigeria. The data were collected from respondents via the use of questionnaires, and were analysed using SPSS and Smart PLS 3.0. Evidence put forward indicated that for female Entrepreneurs in Nigeria to succeed in running their businesses effectively and efficiently, they need to equip themselves with necessary competencies. The findings revealed that strategy, opportunity and organizing competencies have positive direct relationship with firm performance.